2011
DOI: 10.1111/j.1749-6632.2011.06293.x
|View full text |Cite
|
Sign up to set email alerts
|

Dropping dead: causes and consequences of vulture population declines worldwide

Abstract: Vultures are nature's most successful scavengers, and they provide an array of ecological, economic, and cultural services. As the only known obligate scavengers, vultures are uniquely adapted to a scavenging lifestyle. Vultures' unique adaptations include soaring flight, keen eyesight, and extremely low pH levels in their stomachs. Presently, 14 of 23 (61%) vulture species worldwide are threatened with extinction, and the most rapid declines have occurred in the vulture-rich regions of Asia and Africa. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
395
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 373 publications
(414 citation statements)
references
References 70 publications
7
395
0
12
Order By: Relevance
“…The turkey vulture is the world's most abundant and widely distributed obligate avian scavenger, and appears to be adapting to or pre-adapted to human-caused changes in the environment better than its Old World counterparts, many of whom are facing steep population declines [25]. The species' global population, which exceeds five million individuals, appears to be increasing.…”
Section: Materials and Methods (A) Study Species: Turkey Vultures (Catmentioning
confidence: 99%
See 1 more Smart Citation
“…The turkey vulture is the world's most abundant and widely distributed obligate avian scavenger, and appears to be adapting to or pre-adapted to human-caused changes in the environment better than its Old World counterparts, many of whom are facing steep population declines [25]. The species' global population, which exceeds five million individuals, appears to be increasing.…”
Section: Materials and Methods (A) Study Species: Turkey Vultures (Catmentioning
confidence: 99%
“…Alternatively, decreases in primary productivity driven by drought may increase the need for larger home ranges leading to increased competition, which may reduce the population density. That said, the enormous variability we have uncovered in the movement ecology of this species suggests that it is likely to do well in the face of global change, and that unless other human-related threats [25], including environmental toxicants or increased direct human persecution, intervene, the species is likely to remain widespread and abundant across much of its current range. Whether other partial migrants will fare as well is likely to depend on the extent of variability in their migration syndromes.…”
Section: (C) Environmental Drivers Of Migratory Movementmentioning
confidence: 99%
“…9 Regular consumption of livestock remains places scavenging birds at heightened risk of exposure to veterinary drug residues, as evidenced by vulture die-offs from diclofenac toxicity on the Indian subcontinent. 9 A Canadian study found that wildlife residing near livestock operations exhibited greater antimicrobial resistance relative to other habitats.…”
Section: Brief Communicationmentioning
confidence: 99%
“…Increasing independence in this population has contributed to recent increases in lead-related mortality, which are also likely evident from improved detection in the post-ban period with fewer deaths from undetermined causes. Similar to other vulture populations experiencing declines worldwide (Fisher et al, 2006;Ogada et al, 2012;Shultz et al, 2004), California condors are susceptible to large-scale poisoning events as a result of communal foraging behavior that puts several individuals at risk of exposure to a single contaminated carcass (Ogada et al, 2012). Progress toward recovery is not sustainable if the level of management required to ameliorate the threat of lead poisoning for the condor population remains the same, as the majority of investment has been put forth to reducing mortality rates rather than improving the viability of the reintroduced populations (Walters et al, 2010).…”
Section: Resultsmentioning
confidence: 77%